The Effectiveness of an Application Supporting Augmented Reality Technology in Developing Scientific Thinking Skills and Scientific Concepts in the Topic of Science and Life for Fifth-Grade Students in Gaza - Zaqout , Yasmin Jamal; AL-Naqa, Salah Ahmad; Aqeil , Magdy Said (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to examine the effectiveness of an application supporting augmented reality technology in developing scientific thinking skills and scientific concepts among fifth-grade students in Gaza, Palestine. Methods: The researchers employed an experimental approach, with a study sample consisting of 60 female students from the fifth grade at Cairo Basic School "A" for girls during the academic year 2018/2019. These students were randomly divided into experimental and control groups, with each group comprising 30 students. Pre- and post-tests were conducted to measure scientific thinking skills and scientific concepts. The experimental group received instruction using an application that supports augmented reality technology, while the control group was taught using traditional methods. Results: The findings revealed statistically significant differences at the (α = 0.05) level between the mean scores of the two tests (scientific thinking skills and scientific concepts) for the experimental and control groups, favoring the experimental group. Additionally, the gain rate for Blackback in testing scientific thinking skills and scientific concepts exceeded 1.2, indicating the application’s effectiveness. Conclusions: It is recommended that educators consider incorporating the suggested application into their teaching practices. Furthermore, the Palestinian Ministry of Education should organize training courses for students and teachers to effectively utilize this technology.